PENGARUH TRANSAKSI TRANSFER PRICING, INVENTORY INTENSITY, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurhakim Nurhakim (JURNAL KINDAI, 2023)
The purpose of this study was to analyze the effect of transfer price transactions, inventory intensity and capital intensity on corporate tax avoidance. The research population consisted of all companies engaged in the oil palm plantation sector registered on the BEI from 2019 to 2022. Using the purposive sampling method, 41 samples were obtained from 15 companies in the oil palm plantation sector. The data analysis technique used is descriptive statistics, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, coefficient of determination test, model feasibility test, partial test and multiple linear regression analysis. The results of this study indicate that there is no significant effect between the variables of transaction transfer prices and capital intensity on tax evasion in the observed sample. While inventory intensity has a significant effect on tax avoidance. However, to gain a more comprehensive understanding of this relationship, further research is needed by considering larger sample sizes, relevant contextual factors and more appropriate analytical approaches.